The Information Technology Effect, Quality Service, and Tax Sanctions on PBB Tax Compliance - Jannah, Siti Miftachul; Kistyanto, Anang; Witjaksono, Andre Dwijanto (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study examines the impact of tax information technology services and tax sanctions on property taxpayers' (UN) compliance in Surabaya. Using multiple linear regression, the research finds that tax information technology, service quality, and sanctions all significantly and positively influence tax compliance. Efficient e-filing and e-payment systems enhance reporting accuracy, making compliance more transparent. High-quality services from tax authorities, marked by responsiveness and reliability, increase taxpayer trust, leading to better compliance. Fair and transparent sanctions act as a deterrent, promoting adherence to tax regulations. The study concludes that Surabaya's tax authorities should focus on advancing technology, enhancing service quality, and enforcing consistent sanctions to improve compliance. Recommendations include investing in technology, training tax officers, and strengthening law enforcement. This research offers insights into tax policy in Surabaya and other areas, highlighting the factors that drive local tax compliance and setting the stage for future studies on the relationship between technology, services, and sanctions in enhancing tax compliance.